Isolation of Undifferentiated Female Germline Cells from Adult Drosophila Ovaries. (3rd August 2015) - Lim, Robyn Su May; Osato, Motomi; Kai, Toshie
Abstract: This unit describes a method for isolating undifferentiated, stem cell–like germline cells from adult Drosophila ovaries. Here, we demonstrate that this population of cells can be effectively purified from hand‐dissected ovaries in considerably large quantities. Tumor ovaries with expanded populations of undifferentiated germline cells are first removed from fly abdomens and dissociated into a cell suspension with the aid of protease treatment. The target cells, which express Vasa‐green fluorescent protein (GFP) fusion protein under the control of the germline‐specific vasa promoter, are specifically selected from the suspension via fluorescence‐activated cell sorting (FACS). These protocols can be adapted to isolate other cell types from fly ovaries, such as somatic follicle cells or escort cells, by driving GFP expression in the respective target cells. © 2015 by John Wiley & Sons, Inc.